The Influence Rinsing Roselle (Hibiscus Sabdariffa) Boiled Water to Bacterial Colonies in Oral Cavity - Annisa Pertiwi; Adi Prayitno; Marwoto . (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2016)
Introduction: Roselle (Hibiscus sabdariffa L.) is a herb plant that is widely consumed by society. Its flower contains some compounds that have antibacterial activity. Those compounds are flavonoid, phenol, tannin, and saponin. One of the main problems of the oral healthiness is gingivitis. In oral cavity of the gingivitis patients, there is an escalation of the number of bacterial colonies. Whereas using mouthwash is one of the ways to maintain the health of oral cavity. This study aimed to determine the influence of rinsing with roselle flower boiled water to the number of bacterial colonies in oral cavity. Methods: This research was an experimental analytic study with the pre test and post test controlled group design. There were 20 subjects that meet the criterias, they were divided randomly into 2 groups, each group consisting 10 subjects. Firstly, each group was once rinse with 15 ml distilled water for 30 seconds then the rinsing results were put inside the sterile pots. After that, group I was once rinse with 15 ml distilled water for 30 seconds, whereas the group II was rinse with 15 ml roselle flower boiled water for 30 seconds. The level of roselle in this research is 1,5 grams in 15 ml water. The rinsing results were carried to Microbiology Laboratory to put onto the nutrient agar then were incubated for 24 hours in 37C. The differences between the first rinse and the second rinse were calculated. The data were analyzed with SPSS 22.0 for Windows. Results: The results were tested with linear regression test. It showed that roselle has the influence to inhibits the growth of bacterial colonies in the amount of 88%, whereas the 12% is influenced by other factors (e.g. degrees of acidity, the ability of the subjects in rinsing to reach the bacterias). Conclusions: It can be concluded that there is influence rinsing with roselle flower boiled water to the number of bacterial colonies in oral cavity. Keywords: roselle, bacterial colonies, oral cavity